A fundamental optimization study on chewing gum textural and sensorial properties: The effect of ingredients - Palabiyik, Ibrahim; Guleri, Tuba; Gunes, Recep; Oner, Baris; Toker, Omer Said; Konar, Nevzat (ELSEVIER, 2020)
The composition of chewing gum and the interaction between its components are quite complex. Although these factors have great importance on product quality, they have not been adequately studied. In this study, effects of the content of minor (lecithin, sorbitol, glycerin) and major ingredients (gum base, powdered sugar, and glucose syrup) of chewing gum on textural and sensorial properties were investigated by D-optimal mixture design approach. According to the results, powdered sugar and lecithin generally increased aroma durability during chewing, and glucose syrup increased the softness and chewability of the gum. It was revealed that the hardness and resilience texture parameters are the most important parameters to determine appropriate sensorial texture in chewing gum. The optimum composition causing the best liking for aroma duration was found as 17.9 % gum base, 25.65 % glucose syrup, 55.15 % powdered sugar, 0.3 % lecithin, 0 % glycerin, and 0 % sorbitol.
Keywords: Chewing gum; Texture; Sensory; D-optimal mixture design; Ingredients; Food Science & Technology